Вплив лозартану на ультраструктурну морфологію формених елементів крові у хворих на цукровий діабет та артеріальну гіпертензію - Т. О. Pertseva; T. S. Turlyun (Medičnì Perspektivi, 2013)
Ultrastructural changes of blood cells in with patients with hypertension of 1-2-degree, in patients with diabetes mellitus type 2 at compensation and subcompensation phase as well as in patients with diabetes mellitus and hypertension during correction of blood pressure with losartan was defined. It is shown that in patients with hypertension of 1-2-degree relative content of activated platelets does not differ from the normal level. In patients with diabetes mellitus type 2 at compensation or subcompensation phase increase of degree of platelet activation, regardless of presence (150.9%) or absence of hypertension (141.5%) is observed. Conducted antihypertensive therapy does not affect the spontaneous activation of platelets within 1 year. In patients with hypertension potential aggregation of platelets is the most sensitive element of platelet hemostasis damage, which can be normalized beginning with 6-th month of losartan treatment. In patients with diabetes mellitus type 2 with hypertension elevation of platelet aggregation is the most significant (75.4%) and a reliable effect of antihypertensive therapy on limitation of platelet aggregation is achieved in 9 months of treatment. The degree of platelet degranulation is not different from the norm in patients with hypertension and significantly elevated in patients with diabetes mellitus type 2 (by 81.0%), during 1-year observation a constant level of the parameter is revealed. In the group of patients with diabetes mellitus and hypertension, where the original content of degranulated platelets is sharply increased (by 76.2%), a significant positive dynamics in the course of treatment with losartan is observed.